Propedeutics of series in a school - Mačys, Juozas Juvencijus; Sušinskas, Jurgis (Lietuvos matematikos rinkinys, 2013)
By examples of series for number π and number e we demonstrate that in a school one can to interpret series as mnemonic rules or as systems of double inequalities.
Keywords: number pi; number e; series; mnemonic rule; double inequality